2020
DOI: 10.1186/s13705-020-00271-4
|View full text |Cite
|
Sign up to set email alerts
|

Heat consumption scenarios in the rural residential sector: the potential of heat pump-based demand-side management for sustainable heating

Abstract: Background Poor air quality and inadequate domestic heating sources are tightly connected problems in the Eastern-European countryside. There are a few alternatives to comprehensively solve these problems with an emphasis on economic and environmental sustainability. In this paper, individual heat pumps and energy efficiency measures are analyzed in four scenarios to investigate their role for cleaner and sufficient heating in rural settings. From a high-level perspective, this paper assesses the potential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…As regards the combustion efficiency, for the centralized heating systems we consider the percentage distribution relative to 2003 [19], for which the efficiency is for 5.15% of the boilers less than 0.85, for 26.97% between 0.85 and 0.9, for 62.87% between 0.90 and 0.95 and for 5% above 0.95. For individual systems, table 3 shows the data of [11], for boilers maintained and not, by year of installation.…”
Section: Tablementioning
confidence: 99%
“…As regards the combustion efficiency, for the centralized heating systems we consider the percentage distribution relative to 2003 [19], for which the efficiency is for 5.15% of the boilers less than 0.85, for 26.97% between 0.85 and 0.9, for 62.87% between 0.90 and 0.95 and for 5% above 0.95. For individual systems, table 3 shows the data of [11], for boilers maintained and not, by year of installation.…”
Section: Tablementioning
confidence: 99%
“…DR can be modeled using the elasticity matrix of the electricity prices of the load demands. 4,5 Using a constant elasticity matrix over a pre-determined period of time, it was concluded by various studies [6][7][8][9][10][11] that DR has a significant positive impact on the electricity market prices, reliability, and spinning reserves issues. However, this assumption of fixed elasticity of specific over specific time results in the incredibility of EVs of the proposed methods.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34] The optimal charging management was investigated by Mkahl et al 35 Similar work was achieved by Bin-Humayd and Bhattacharya. 36 The parking coordination of EVs was investigated in the study by Faddel et al 37 The investigation of the above research [2][3][4][5][6][7][8][9][10][11][12][13][15][16][17] reveals that a constant elasticity matrix for a specific interval of time was used, which results in some incredibility. In the study by Srivastava et al, 14 regression methods generally need training, and the accuracy of the regression models depends on the number of available data.…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al (Ali et al 2014) proposed that electric heating and thermal storage, when sued in series, can achieve an optimal demand response in smart grid scenarios by simulating and analyzing heat demand and power. Campos et al (Campos et al 2020) conducted energy analysis and prediction for rural heating in Hungary; they suggested that a combination of electric energy retrofitting and efficient heating technologies can be used to meet rural heating.…”
Section: Introductionmentioning
confidence: 99%